2022
DOI: 10.3390/healthcare10101847
|View full text |Cite
|
Sign up to set email alerts
|

How Has COVID-19 Changed the Way We Do Virtual Care? A Scoping Review Protocol

Abstract: The coronavirus disease (COVID-19) pandemic created worldwide interest and use of virtual care to support public health measures and reduce the spread of infection. While some forms of virtual care have been used prior to COVID-19 such as telemedicine, little is known about other virtual modalities such as video conferencing, wearables and other digital technologies. The COVID-19 pandemic has presented an opportunity to question the efficacy and safety of virtual care, especially in terms of patient outcomes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Following 2 levels of screening, 19 articles meeting the eligibility criteria were included. 23 Table 1 presents an outline of the included articles and whether patient experiences and/or preferences were addressed. Only 1 study indicated patient experience as a primary outcome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following 2 levels of screening, 19 articles meeting the eligibility criteria were included. 23 Table 1 presents an outline of the included articles and whether patient experiences and/or preferences were addressed. Only 1 study indicated patient experience as a primary outcome.…”
Section: Resultsmentioning
confidence: 99%
“…25 The complete methods for the scoping review were published separately as a protocol. 23 In consultation with a health librarian, a comprehensive search strategy was developed. Four bibliographic databases (CINAHL, Medline, Emcare, and Cochrane Database of Systematic Reviews) were searched between January 30, 2022 and February 3, 2022 for literature published in English between 2020 and 2022.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, other researchers might benefit from accessing this kind of publication to help structure methodological reproducibility for umbrella reviews in mental or psychiatric conditions [ 39 , 40 ]. Even though the definition of research questions, population, outputs, and timeframe, are well described in the PICOT table, in previous protocols, researchers report a moderate level of disagreement about which articles to include or exclude [ 35 ]. This suggests that reliability across researchers should be improved after further meetings to discuss disagreements under this protocol application…”
Section: Discussionmentioning
confidence: 99%
“…To summarize the process, a PRISMA flowchart presenting the sequence of manuscripts selected at each screening level will be included according to the procedures of several authors, such as Catallo et al, 2022 [ 35 ].…”
Section: Methodsmentioning
confidence: 99%